Plasma Phospholipid Saturated Fatty Acids and Incident Atrial Fibrillation: The Cardiovascular Health Study. Issue 3 (26th June 2014) - Fretts, Amanda M.; Mozaffarian, Dariush; Siscovick, David S.; Djousse, Luc; Heckbert, Susan R.; King, Irena B.; McKnight, Barbara; Sitlani, Colleen; Sacks, Frank M.; Song, Xiaoling; Sotoodehnia, Nona; Spiegelman, Donna; et al.
Abstract : Background: Prior studies suggest that circulating fatty acids may influence the risk of atrial fibrillation (AF), but little is known about the associations of circulating saturated fatty acids with risk of AF. Methods and Results: The study population included 2899 participants from the Cardiovascular Health Study, a community‐based longitudinal cohort of adults aged 65 years or older in the United States who were free of prevalent coronary heart disease and AF in 1992. Cox regression was used to assess the association of all the long‐chain saturated fatty acids—palmitic acid (16:0), stearic acid (18:0), arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0)—with incident AF. During a median of 11.2 years of follow‐up, 707 cases of incident AF occurred. After adjustment for other AF risk factors, higher levels of circulating 16:0 were associated with a higher risk of AF (hazard ratio comparing highest and lowest quartiles: 1.48; 95% CI: 1.18, 1.86). In contrast, higher levels of circulating 18:0, 20:0, 22:0, and 24:0 were each associated with a lower risk of AF. The hazard ratios (95% CI) for AF in the top and bottom quartiles were 0.76 (95% CI: 0.61, 0.95) for 18:0; 0.78 (95% CI: 0.63, 0.97) for 20:0; 0.62 (95% CI: 0.50, 0.78) for 22:0; and 0.68 (95% CI: 0.55, 0.85) for 24:0. Conclusions: Results from this prospective cohort study of older adults demonstrate divergent associations of circulating 16:0 versus longer‐chain saturated fatty acids with incident AF, highlighting the need to investigate both determinants of these levels and potential pathways of the observed differential risk.